A Study of the Hydrodynamics Behavior of Cylindrical Gas-Solid Fluidized Beds for pharmaceutical material “Paracetamol “ (Journal of Engineering, 2020)
The hydrodynamics behavior of gas - solid fluidized beds is complex and it should be analyzed  and understood due to its importance in the design and operating of the units. The effect of column inside diameter and static bed height on the minimum fluidization velocity, minimum bubbling velocity, fluidization index, minimum slugging velocity and slug index have been studied experimentally and theoretically for three cylindrical columns of 0.0762, 0.15 and 0.18 m inside diameters  and 0.05, 0.07 and 0.09 m static bed heights .The experimental results showed that the minimum fluidization and bubbling velocities had a direct relation with column diameter and static bed height .The minimum slugging velocity had an inverse relation with static bed height and a direct one with column diameter .There was no agreement between the experimental and calculated values of Umb for Di=0.0762m ,this was a result to the assumption used in the correlation development. The fluidization index values were around 1 in all cases and that proved that the material is of Geldart type B. There was not a significant dependence of fluidization index and slug index on static bed height and column diameter.